PENGARUH PENERAPAN TEKNIK PASAR TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IPA SMAN 15 PADANG - Fitriana, Melisa; Rismen, Sefna; Lovia, Lita (STKIP PGRI Sumbar, 2014)
ABSTRACTThe research were background by the students who passive in process of study and studentsâ comprehension of mathematical concept that still low. This research were aim to know how to increased students activity use Teknik Pasar and also to know whether studentsâ comprehension of mathematical concept by implementing Â Teknik Pasar was better than implementing conventional learning in class XI IPA SMAN 15 Padang. This was an experimental research which used random to subject. Observation sheet analysis result obtained that studentsâ activity was increased in every meeting. Hypothesis test used t-test one way with minitab Software, obtained that tvalue = 1,94 and ttable = 1,668 with Â = 0,05. Because of tvalue Â ttable, then H0 was rejected. It can be conclude that studentsâ comprehension of mathematical concept by implementing Teknik Pasar was better than studentsâ comperehension of Â mathematical concept by implementing conventional in class XI IPA SMAN 15 Padang.